Endocarditis of a congenital coronary fistula in a child. (11th September 2017) - Krasemann, Thomas; van Beynum, Ingrid M.; Frohn-Mulder, Ingrid M. E.; Dalinghaus, Michiel
Abstract: Endocarditis of congenital coronary fistulas in the cardiac chambers is rare, especially in the paediatric age group. We describe the case of a 9-year-old boy with a fistula from the dilated right coronary artery to the junction of the superior caval vein to the right atrium, complicated by endocarditis. Treatment consisted of 6 weeks of antibiotics and interventional closure of the fistula 3 months later with an Amplatzer vascular plug.